Biological Analysis of Mackerel Tuna (Euthynnus affinis) in Banda Sea Waters - Ahmad, Sitti Wirdhana; Amirullah, Amirullah; Nur, Andi Irwan; Amalia, Kartika; Nasaruddin, Nasaruddin; Izal, Izal; Rudia, Adi Parman (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2024)
Mackerel tuna (Euthynnus affinis) is a significant fishery commodity in the Banda Sea, part of Fisheries Management Area 714 (WPP 714). This study focused on analyzing the biological characteristics of mackerel tuna, including length-frequency distribution, recruitment patterns, growth parameters, and mortality rates. Research was conducted at the Kendari Ocean Fisheries Port (PPS), with catch data from the Banda Sea provided by PPS Kendari observers. Data were analyzed using Microsoft Excel and software applying Von Bertalanffy's growth model. Fish length increased throughout the year, with the highest frequency observed from April to May and an average length of 50 cm. Recruitment patterns revealed two annual peaks in March and August. The growth constant (K) was 0.632, with a growth index of 1.0. Mortality analysis showed total mortality (Z) at 6.70, natural mortality (M) at 1.24, fishing mortality (F) at 5.46, and an exploitation rate (E) of 0.82. These results suggest that while growth rates remain favorable, mackerel tuna is experiencing overexploitation, highlighting the need for sustainable fisheries management.